Study on precision reliability evaluation method of harmonic drive based on NIPCE considering wear - Xian Zhang; Changming Zhang; Peng Wang; Chunlei Peng; Fan Yang (Scientific Reports)
Abstract A dynamic reliability evaluation method for precision of harmonic drive considering wear is proposed to estimate the precision reliability of harmonic drive precisely for precision degradation failure prediction and proactive maintenance. Firstly, according to the transmission error components caused by contact pair wear of harmonic drive, a dynamic model of harmonic drive considering contact pair wear is established. Then a Non-Intrusive Polynomial Chaos Expansion(NIPCE) based uncertainty analysis method is proposed for transmission precision response solution of harmonic drive dynamic model under multi-dimensional random variables, and the efficiency of uncertainty analysis is further improved by introducing sparse grid. Finally, combined with Monte Carlo simulation, a precision dynamic reliability evaluation method based on the explicit surrogate model from polynomial chaos expansion is established. The results show that the contact pair wear of flexspline(FS) and Circular Spline(CS) plays a bigger role in the precision reliability compared with the contact pair wear of flexspline and Wave Generator(WG); the precision dynamic reliability result in this paper has the same variation trend as the precision dynamic reliability deduced from the precision degradation test, which verified the effectiveness of the proposed method.